Case report: Hypertrophic lichen planus initially misdiagnosed as squamous cell carcinoma - Kuchimanchi, Nidhi; Luu, Lydia A.; Shah, Preeya T.; DeSimone, Jennifer (Frontiers in Medicine, 2024)
Fewer than 26 case reports describe hypertrophic lichen planus (HLP) misdiagnosed as cutaneous squamous cell carcinoma (cSCC). It can be difficult to distinguish between HLP and cSCC, as these two conditions share many clinical and histopathological characteristics. Patients who are misdiagnosed with cSCC often undergo unnecessary medical and/or surgical interventions before receiving a diagnosis of HLP and improving on HLP-directed therapy. This case series highlights the course of three female patients, referred to a single tertiary institution between 2018 and 2022, who were initially misdiagnosed with cSCC before receiving a diagnosis of HLP. We have emphasized the clinical and histopathological distinguishing features between HLP and cSCC, the pathogenesis of HLP, and current and new HLP-directed therapy. We hope that this case series serves as a reminder to dermatologists, dermatologic surgeons, and dermatopathologists to be aware of this diagnostic challenge.